Implementation of Qiyas Dalil in Istinbath Contemporary Muamalah Law - Yani, Sirajul; Septyanun, Nurjannah; Halim, Andy Fahmi (Universitas Muhammadiyah Surakarta, 2024)
Qiyas is one of the methods of ruling in Islam that is used to determine the rulings of contemporary cases that do not have a direct text from the Qur'an and Sunnah. There are many contemporary cases that require a qiyas approach in determining the law. Therefore, this research is important to do in order to fill the void. This research is a descriptive qualitative research with a literature study approach. This approach is used to analyze the application of qiyas in contemporary muamalat based on the opinions of classical and contemporary scholars, as well as studies from fatwas of sharia institutions. This data is taken from various sources of literature relevant to the topic of qiyas, such as books of ushul fiqh, the views of fuqaha, and fatwas issued by sharia institutions, such as AAOIFI and Majma' Fiqh Islami. The stages of research are the stages of collecting literature data (library research), data validation, through triangulation. The next stage of data analysis and interpretations and the preparation of conclusions by systematically examining the application of qiyas in contemporary muamalat is carried out using qualitative descriptive analysis methods. The result of the study is that qiyas is defined as the similarity of the branch to the origin in terms of legal illat. The urgency of qiyas in contemporary muamalat law is crucial, especially due to the limitations of nash and ijma. Qiyas plays an important role in providing sharia legal certainty for various cases that continue to develop. The views of classical and contemporary scholars on the importance of qiyas in determining Islamic law, as well as several related fatwas issued by world fatwa institutions, are the basis for determining (istinbath) the law. With qiyas, Islamic law remains relevant to be applied in modern economic transactions. The application of qiyas in various contexts of contemporary muamalat, such as the qiyas of currency with dinars and dirhams, the validity of cash waqf with qiyas against weapons of war, as well as the validity of service lease transactions and qiyas on salam contracts. The application of qiyas leads to the determination of certain laws and leads to legal certainty regarding the contemporary issue in question.